Molecular diagnosis of Myxobolus spirosulcatus associated with encephalomyelitis of cultured yellowtail, Seriola quinqueradiata Temminck & Schlegel - Yokoyama, H.; Yanagida, T.; Freeman, M.A.; Katagiri, T.; Hosokawa, A.; Endo, M.; Hirai, M.; Takagi, S. (Blackwell Publishing, 2010)
Mass mortality of cultured yellowtail, Seriola quinqueradiata, has recently been reported from fish farms in western Japan. Previous studies revealed that diseased fish were characterized by encephalomyelitis and presporogonic stages of a myxosporean-like parasite in the spinal cord. However, the parasite has remained unidentified because of the lack of mature stages being present. Thus, in the present study, analysis of the small subunit ribosomal DNA (18S rDNA) of the parasite as well as in situ hybridization (ISH) studies using histological sections of the infected tissue was conducted. The 18S rDNA of the myxosporean had higher sequence similarities with those of bile-duct-infecting myxosporeans rather than those infecting nervous tissues and was identified as Myxobolus spirosulcatus. The ISH using specific probes demonstrated that the DNA amplified was derived from the multinuclear organisms found in histological sections. A highly sensitive and specific PCR-based assay for M. spirosulcatus was developed, which revealed a high prevalence of infection in cultured yellowtail that exhibited the clinical signs of encephalomyelitis.